Management of type 2 diabetes using non‐insulin glucose‐lowering therapies: a critical appraisal of clinical practice guidelines with the AGREE II instrument. Issue 4 (27th January 2020) - Lam, W. M. J.; Al‐Khalifah, R.; Florez, I. D.; Cruz‐Lopes, L.; Sekercioglu, M. F.; Couban, R.; Fu, R.; Cherney, D. Z. I.; Sekercioglu, N.
Abstract: Aim: Type 2 diabetes is a major global epidemic affecting over 400 million people worldwide. The objective of this systematic review was to provide an overview of recommendations from clinical practice guidelines (guidelines) addressing non‐insulin based pharmacological management of among non‐pregnant adults in an outpatient setting, and critically appraise their methodological development. Methods: We systematically searched MEDLINE and Embase databases, for relevant guidelines using the Ovid interface. We scanned the bibliographies of all eligible guidelines for additional relevant citations. Teams of two reviewers, independently and in duplicate, screened titles and abstracts and potentially eligible full text reports to determine eligibility and appraised the reporting quality of guidelines using the Advancing Guideline Development, Reporting and Evaluation in Health Care instrument II (AGREE II) instrument. Results: Our search yielded 11264 unique citations, of which 124 were retrieved for full‐text review; 17 guidelines proved eligible. The highest scoring AGREE domain was 'clarity of presentation' (66%; range 7–92%), followed by 'scope and purpose' (58%; range 25–92%), 'editorial independence' (55%; range 0–91%), 'stakeholder involvement' (45%; range 11–90%) and 'rigour of development' (43%; range 4–92%). The poorest domain was 'applicability' (37%; range 6–84%). The guidelines authored by the World Health Organization group achieved the highest AGREE overall score. Conclusions: Most of the guidelines provided recommendations with a local jurisdictional focus and showed significant variation in the quality. Nevertheless, only a small number of those scored well overall. What's new?: Evidence‐based guidelines limit unnecessary variation in clinical practice and supposedly improve outcomes important for the person with diabetes. We performed a systematic review to provide an overview of recommendations from guidelines for type 2 diabetes and critically appraised their methodological development using the Advancing Guideline Development, Reporting and Evaluation in Health Care instrument II (AGREE) instrument. Our study showed recommendations of the guidelines on the management of type 2 diabetes were consistent, suggesting a consensus in the clinical community with regards to first‐line therapy despite the absence of high‐quality evidence. The major limitation of current guidelines was poor quality according to the AGREE criteria and inconsistent recommendations with regards to second‐line therapy.